KARAKTERISASI DAN ANALISIS POLA PERTUMBUHAN IKAN KEMBUNG (Rastrelliger sp.) YANG DIDARATKAN DI TEMPAT PELELANGAN IKAN KEDONGANAN, BALI: CHARACTERIZATION AND GROWTH PATTERN ANALYSIS OF IKAN KEMBUNG (Rastrelliger sp.) LANDED AT KEDONGANAN FISH AUCTION SITE, BALI - Revael Sihombing; Ni Made Suartini; Ngurah Intan Wiratmini (SIMBIOSIS, 2025)
ABSTRACT One of Bali's largest fish potential areas is Kedonganan, a coastal region where the majority of residents are fishermen. Kedonganan waters represent a highly promising fish landing site due to its direct proximity to the Indian Ocean. Based on preliminary surveys and interviews with local fishermen, the dominant small pelagic fish species frequently landed in large quantities at the Kedonganan Fish Auction (TPI) are mackerel fish (Rastrelliger sp.). This study aims to investigate the morphology, morphometrics, and growth patterns of these species landed at TPI Kedonganan. This research employed survey and interview methods. The variables examined include fish morphology, fish morphometrics consisting of 15 characters, and the growth patterns of mackerel fish (Rastrelliger sp.). The findings reveal that mackerel fish (Rastrelliger sp.) exhibit a fusiform body shape, terminal mouth, forked caudal fin, and cycloid scales. Morphometric measurements showed an average total length of 217.8 cm. The growth pattern of mackerel fish includes negative allometric (b<3).